The influence of capital structure and operational performance on financial performance with governance and financial risk as mediation in Insurance Companies in Indonesia - Sumarlan, Ahmad; Kamaluddin, Kamaluddin; Fachruzzaman, Fachruzzaman; Robinson, Robinson (Privietlab, 2024)
This study examines the influence of capital structure and operational performance on financial performance, with governance and financial risk as mediators. The sam- ple for this research comprises insurance companies listed on the Indonesia Stock Exchange in 2013-2021 with a total of 72 firm-year observations. The data used are secondary data obtained from annual and financial reports accessed via idx.co.id. The independent variables are capital structure, measured using the Debt Equity Ratio (DER), and operational performance, measured using liquidity. The mediating variable is the governance variable, measured by the independent board of directors (DKI), and financial risk is measured using Risk Based Capital (RBC). The depen- dent variable in this study uses financial performance as measured by Return On Assets (ROA). The results prove the following: (1) Capital structure has a positive and significant effect on financial performance. (2). Operational performance has a negative and significant effect on financial performance. (3). Capital structure had a positive and significant effect on DKI. (4) Operational performance has a significant negative effect on financial risk. (5) DKI does not mediate the influence of capital structure on financial performance. (6) Financial risk fully mediates the influence of operational performance on financial performance. (7). DKI has a negative and significant effect on financial performance. (8). Financial risk has a negative and significant effect on financial performance.